2021
DOI: 10.1097/j.jcrs.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of residual astigmatism on uncorrected visual acuity and patient satisfaction in pseudophakic patients

Abstract: In pseudophakic patients, even low amounts of residual astigmatism can increase the odds of not achieving 20/20 or 20/16 uncorrected distance visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…Among all subjects, 22.4% of the eyes had an ORA magnitude of 1.0 D or more, which was consistent with previous studies ( 4 , 28 ) reporting an ORA magnitude larger than 1.0 D in about one-third of the eyes. A growing number of evidence have shown that postoperative patients with uncorrected astigmatism error of 1.0 D or even less had symptoms of blurred vision and eye fatigue ( 6 , 7 , 30 ). Thus, better management of ORA is important for surgeons to achieve satisfactory postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all subjects, 22.4% of the eyes had an ORA magnitude of 1.0 D or more, which was consistent with previous studies ( 4 , 28 ) reporting an ORA magnitude larger than 1.0 D in about one-third of the eyes. A growing number of evidence have shown that postoperative patients with uncorrected astigmatism error of 1.0 D or even less had symptoms of blurred vision and eye fatigue ( 6 , 7 , 30 ). Thus, better management of ORA is important for surgeons to achieve satisfactory postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…ORA is known as the vectoral difference between ACA and MA at the corneal plane ( 3 , 4 ). This difference may result in excess corneal astigmatism and resultant glare, starburst, and haloes (GASH), leading to reduced visual acuity and even visual fatigue after refractive surgery ( 5 7 ). Therefore, appropriate management of ORA has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings also suggested a positive association between visual acuity and astigmatism (LogMAR acuity = 0.068 + 0.055 astigmatism) ( 13 ). Moreover, a case-control study revealed that low-level ORA induced by IOL implantation in patients also reduced their visual acuity ( 14 ). The reason is that astigmatism could prevent the human eye from focusing complex visual information on the retina, leading to blurred vision.…”
Section: Discussionmentioning
confidence: 99%
“…And this can be in part the cause of halos in our patients. However, in a recent study, it was described that the effect of residual astigmatism on visual performance and satisfaction was more evident at the 0.75 to 1.00 D.[ 35 ] Finally, the authors conclude that corneal astigmatism of 0.50 or higher must be considered to be included and managed in the surgical plan. It is an interesting point, but in our case, we have not managed that: limbal relaxing incisions were not performed and the toric option was not available when the study was conducted.…”
Section: Discussionmentioning
confidence: 99%